Prinsip-Prinsip Islam Dalam Pengembangan Manajemen Mutu Pendidikan Di Smp Muhammadiyah Boarding School (Mbs) Cepu Blora Tahun 2015 - Syaidin, Mukhammad (2016)
ABSTRACT Quality management in the context education have range that cover education process sort that is carried on in one education institute. That management covers planning, organizing, powering, and observation. In performing processes education, SMP Muhammadiyah Boarding School (MBS) Cepu Blora that constitute Islamic education institute of course it have characteristic in schooled management. Points in Islam of course it does ever be made footing in do education institute management this. It is constituted because Boarding School on its reality constitute education that carried on by one education institute that bands among student home with education process. The problem that emerging in education management development at SMP Muhammadiyah Boarding School (MBS) Cepu Blora get bearing with education management namely is still visually mark sense severally job post that insufficiently corresponds to its membership area, and exists task denotation without mark sense beforehand deliberation element. Observational problem formula this is: 1) How is Islamic principle performings in developmental education quality management at SMP Muhammadiyah Boarding School (MBS) Cepu Blora?; 2) Whatever resistor factor and Islamic principle performing supportings in developmental education quality management at SMP Muhammadiyah Boarding School (MBS) Cepu Blora?. To the effect in this research is subject to be know Islamic principle performings in developmental education quality management and to know resistor factor and Islamic principle performing supportings in developmental education quality management at SMP Muhammadiyah Boarding School (MBS) Cepu Blora The result even that research are: a ) Islamic principles those are carried on in quality management development education at SMP Muhammadiyah Boarding School (MBS) Cepu Blora amongst those apply deliberation principle, professionalism, justice and good example; b ) Islamic principle resistor Factors in developmental management covers undercommunication is consciousness for order at the moment does deliberation, still marks sense emerging difference of opinion upon deliberation and is taken in on deliberations outdoor area, and is still mark sense denotation for severally learns to follow some training and education program just focussed on given teacher. Factor supportinging to cover most actually relocation container has say that centered at sectioned liaison, mark sense facility to interpose opinion upon deliberation. school gives good support of activity finance facet, facility, and infrastucture, and also of learning facet, mark sense collaboration and abreast participates deep succeess deliberation decision of planning phase until activity performing phase.